The winter wedding plan - Miles, Olivia (New York : Forever, 2017)
"Charlotte Daniels has made her share of mistakes, but now that she's a single mom, she vows to do better - and that starts iwth a new career. Working at her sister's event-planning company is just the fresh start she needs. Kate Daniels has finally forgiven Charlotte for her betrayal, but forgetting it is harder. But as the holidays approach and Kate has her own wedding to plan, she has no choice but to turn to Charlotte for help in throwing a high-profile client the holiday party of the season. Charlotte leaps at the chance to redeem herself...until this irresistible client asks her to pretend to be his fiancee for the party. She knows their charade won't come without consequences-not just for her fresh start with Kate, but also for her own daughter. As Kate's wedding draws near and Charlotte's fake romance starts to feel more and more real, will she fall back into the mistakes of her past, or finally prove herself to Kate once and for all?" -- Page [4] of cover.
Includes reading group guide.
Keywords: Man-woman relationships -- Fiction; Weddings -- Fiction; FICTION / Romance / General; Man-woman relationships; Weddings; Romance fiction; Fiction; Love stories; Romance fiction